Hydrothermal synthesis of YVO4:Eu3+ micron-sized spheres and their photoluminescence properties. (5th June 2019) - Zhu, Hongliang; Li, Xue; Liu, Yifu; Chen, Jing; Gao, Linhui; Chen, Jianjun; Lin, Wenxin; Li, Yinkang; Chi, Hongzhong
Abstract: This paper presents two facile hydrothermal routes for the synthesis of YVO4 :Eu 3+ regular micron-sized spheres, in which ethylenediaminetetraacetic acid disodium (Na2 EDTA) as an organic additive and polyvinyl pyrrolidone (PVP) as a nonionic organic additive were used, respectively. Their morphologies, structures, particle size distribution and photoluminescence properties of YVO4 :Eu 3+ phosphors were systematically investigated by field emission scanning electron microscopy (FE-SEM), x-ray powder diffraction (XRD), particle size analyzer and photoluminescence (PL) spectroscopy, respectively. The results of above characterizations showed that the obtained products were phase-pure YVO4 :Eu 3+ uniform spheres with a tetragonal structure and an average diameter range of 1∼3 μ m. Five controlled experiments were performed in the same condition except that none additive or other additives (i.e., sodium dodecyl sulfate (SDS), polyethylene glycol 6000 (PEG-6000), cetyl trimethyl ammonium bromide (CTAB) and sodium citrate) were introduced into the hydrothermal process. Not uniform micron-sized spheres but other morphologies such as nanoparticles or micron-sized cubes were obtained through these controlled experiments, which revealed that Na2 EDTA or PVP was a key factor for the synthesis of the uniform micron-sized spheres. Meanwhile, under the excitation around 275 nm, these spherical Eu 3+ ions doped samples showed enhanced red emission than other samples.